“La aplicación del exequátur como mecanismo eficaz para el cobro de pensiones alimenticias en el extranjero” - Dennys Saúl, Quinzo Andrade (2020)
The present research project called “THE APPLICATION OF EXEQUÁTUR AS AN EFFECTIVE MECHANISM FOR THE RECOVERY OF ALIMONY ABROAD”, is divided into three chapters, as follows: Chapter I, called the international legal procedure of the exequatur, will address the main themes of the subject such as the exequatur background; his concept of various writers; its purpose; the principles of application such as verification of the treaty, principle of reciprocity and international regularity of judgments; Exequatur processing and its requirements. Chapter II, called the Convention on the Obtaining of Food Abroad Elaborated within the United Nations, will analyze issues such as the legal particularities of the international treaty, including international judicial cooperation, sovereignty of the States involved and diligence of exhortation; followed by the principles of application, such as the principle of gentium comites and in good faith; national legal basis of the application; the international legal basis of the application and the benefits of the international treaty. Finally, in Chapter III, called problems in exequatur in the execution of alimony, three important problems will be analyzed, such as lack of information, cumbersome processing and the location of the feeder; with which, the research analysis of this research project will be completed.